Identity Politics Revisited: On Audre Lorde, Intersectionality, and Mobilizing Writing Styles - Ilmonen Kaisa (Sage Publications Ltd, 2022)
Intersectionality’ has taken on a complex position in the field of feminist scholarship over the last decade. Debate on the concept has swung back and forth, from buzzword to harsh critique. Amid these discussions, many feminist scholars have thought about Audre Lorde and the role of her writings in the debates over intersectionality. Lorde’s radical literary feminism has often been seen both as reflecting a politics of identity, on the one hand, and as shifting and situational, on the other. Intersectionality has also been claimed either to be recycling the ideas of identity politics or to be forging new ways to grasp decentered identity positions and power structures. This article aims to tell a story about the roots of intersectionality through – and alongside – the legacy of Lorde’s feminism, by revisiting certain identity-political ideas. The radical nature of Lorde’s thinking is in many ways connected to politicized writing styles and rebellious literary forms. The main focus in this article is therefore extended to cover the role and implications of radical writing styles for intersectionality. The article argues that the oeuvre of telling the story of intersectionality through Lorde’s feminism opens up a new perspective on the genealogy of intersectionality.